Pengaruh Pemberian Kompos Mucuna bracteata Dan Pupuk NPK Terhadap Pertumbuhan Bibit Kakao (Theobroma cacao L.) Pada Tanah Ultisol - Haviz, M Fadil; Wardati, Wardati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Cocoa (Theobroma cacao L.) is one of the plantation commodities that had important role in economic activity in Indonesia as a raw material commonly used for the pharmaceutical, cosmetic, food and beverage industries. Efforts to increase cocoa production on Ultisol soil can required by applying Mucuna bracteata compost and NPK fertilizer. This research is an experimental research that is arranged according to factorial Completely Randomized Design (CRD) by giving a combination of Mucuna bracteata compost treatment (4 levels) and NPK fertilizer (3 levels) with three replication. The fertilizer of Mucuna bracteata compost was carried out one week before planting the sprouts according to the treatment dose. NPK fertilizer was applied one week and three weeks after planting the sprouts according to the treatment dose. The variables observed were seed height, stem diameter, number of leaves every four weeks starting from 4 WAP to 16 WAP while root volume, root shoot ratio and seed dry weight were carried out at the end of the study. Observations were made on all plants. The results showed that the fertilizer of Mucuna bracteata compost had an effect on the observed variables, namely seed height, number of leaves, stem diameter, root volume, root crown ratio and seed dry weight in Ultisol soil. The fertilizer of NPK fertilizer had no effect on seed height, stem diameter, root volume, root crown ratio and dry weight of cocoa seedlings in Ultisol soil. The combination of Mucuna bracteata compost and NPK fertilizer affected the growth of cocoa seedlings in Ultisol soil. The fertilizer of 100 g / plant Mucuna bracteata compost and 4 g / plant NPK fertilizer is the best dose for growing cocoa seedlings in Ultisol soil.Keywords: cocoa, Ultisols, Mucuna bracteata, NPK